Palliative care competencies among medical students - Guirro, Úrsula Bueno Do Prado [UNESP]; Perini, Carla Corradi; Fileno, Luís Otávio Zatorre; Fioravanti, Gustavo Belam; de Siqueira, José Eduardo (FapUNIFESP (SciELO), 2023)
Competencies have been defined as the set of knowledge, skills and attitudes that a professional should acquire to perform a certain work activity. This study aimed to assess competencies in palliative care among students enrolled in a Brazilian medical course. All enrolled students were invited to participate and answer the Palliative Competence Tool. The data obtained were calculated in scores between zero and 100 and compared between the ten competencies and academic cycles. The results showed four patterns, the most frequent being a reduction in scores among students in the basic and intermediate cycles, with partial recovery in the internship. Only ethical competence and decision-making increased in the internship. It was concluded that the acquisition of palliative care competencies in undergraduate medical education remains fragile. New teaching strategies could be adopted to improve their acquisition in the future.
Competencias en cuidados paliativos entre los estudiantes de medicina
Competências em cuidados paliativos entre estudantes do curso de medicina
Keywords: Education, medical; Palliative care; Professional competence